Facilitating informed choice about non-invasive prenatal testing (NIPT): a systematic review and qualitative meta-synthesis of women's experiences - Alexandra Cernat; Chante De Freitas; Umair Majid; Forum Trivedi; Caroline Higgins; Meredith Vanstone (BMC, 2019)
Abstract Background Non-invasive prenatal testing (NIPT) can be used to accurately detect fetal chromosomal anomalies early in pregnancy by assessing cell-free fetal DNA present in maternal blood. The rapid diffusion of NIPT, as well as the ease and simplicity of the test raises concerns around informed decision-making and the potential for routinization. Introducing NIPT in a way that facilitates informed and autonomous decisions is imperative to the ethical application of this technology. We approach this imperative by systematically reviewing and synthesizing primary qualitative research on women's experiences with and preferences for informed decision-making around NIPT. Methods We searched multiple bibliographic databases including Ovid MEDLINE, EBSCO Cumulative Index to Nursing & Allied Health Literature (CINAHL), and ISI Web of Science Social Sciences Citation Index (SSCI). Our review was guided by integrative qualitative meta-synthesis, and we used a staged coding process similar to that of grounded theory to conduct our analysis. Results Thirty empirical primary qualitative research studies were eligible for inclusion. Women preferred to learn about NIPT from their clinicians, but they expressed dissatisfaction with the quality and quantity of information provided during counselling and often sought information from a variety of other sources. Women generally had a good understanding of test characteristics, and the factors of accuracy, physical risk, and test timing were the critical information elements that they used to make informed decisions around NIPT. Women often described NIPT as easy or just another blood test, highlighting threats to informed decision-making such as routinization or a pressure to test. Conclusions Women's unique circumstances modulate the information that they value and require most in the context of making an informed decision. Widened availability of trustworthy information about NIPT as well as careful attention to the facilitation of counselling may help facilitate informed decision-making. Trial registration PROSPERO 2018 CRD42018086261.